Traffic education: a theme to be worked on in experimentation in chemistry (Research, Society and Development, 2020)
This work presents the treatment of the theme Education for Traffic developed with students of the 3rd year of high school in a private school. It aims to work with issues relevant to Traffic Education and Breathalyzer, including the content of organic functions, as well as students' awareness of the subject. The production of data occurred from the activities of the chemistry laboratory, from reflections on the practice performed through the transcription of audios. From the transcription of the speeches, it was carried out in Bardin's Content Analysis and emerged as the following categories: (i) Reflection of the experiment as a positive action for future drivers; (ii) Potentiality of using experimentation in Basic Education; (iii) Work with themes in Basic Education. An analysis of the data infers that the treatment of social themes promotes reflective learning and contributes to the construction of Chemistry concepts.